A Qualitative Analysis of Approaches To Contraceptive Counseling. Issue 4 (10th July 2014) - Dehlendorf, Christine; Kimport, Katrina; Levy, Kira; Steinauer, Jody
<x xml:space="preserve">Abstract</x> CONTEXT Underuse and inconsistent use of contraceptives contribute to the continued high rate of unintended pregnancy in the United States. High‐quality interaction between patient and provider about contraception is associated with improved contraceptive use, yet little is known about how providers support patients in the decision‐making process. METHODS A random sample of 50 family planning visits by patients in the San Francisco Bay Area was selected from a larger sample of 342 audio‐recorded visits to six clinics between 2009 and 2012. In qualitative analysis guided by grounded theory techniques, transcripts were assessed to determine counseling approaches and patterns in the use of these approaches. RESULTS Providers employed three counseling approaches: foreclosed (in 48% of visits), characterized by discussion of few contraceptive methods and method selection by the patient with no involvement from the provider; informed choice (30%), characterized by detailed description of multiple methods, but little or no interaction between the patient and the provider; and shared decision making (22%), characterized by the provider's interactive and responsive participation with the patient in method selection. Use of these approaches varied by patient's age: Women 25 or younger experienced the foreclosed approach more often than older women, and patients older than 35 were far more likely than their younger counterparts to experience the shared decision‐making approach. CONCLUSIONS Most visits did not include interactive engagement between the patient and the provider. Contraceptive counseling interventions should encourage providers to responsively engage with patients of all ages to better meet their contraceptive needs.